Sex differences in brain functional connectivity of hippocampus in mild cognitive impairment - Williamson, Jordan; Yabluchanskiy, Andriy; Mukli, Peter; Wu, Dee H.; Sonntag, William; Ciro, Carrie; Yang, Yuan (Frontiers in Aging Neuroscience, 2022)
Mild cognitive impairment (MCI) is the prodromal stage of Alzheimer’s Disease (AD). Prior research shows that females are more impacted by MCI than males. On average females have a greater incidence rate of any dementia and current evidence suggests that they suffer greater cognitive deterioration than males in the same disease stage. Recent research has linked these sex differences to neuroimaging markers of brain pathology, such as hippocampal volumes. Specifically, the rate of hippocampal atrophy affects the progression of AD in females more than males. This study was designed to extend our understanding of the sex-related differences in the brain of participants with MCI. Specifically, we investigated the difference in the hippocampal connectivity to different areas of the brain. The Resting State fMRI and T2 MRI of cognitively normal individuals (n=40, female=20) and individuals with MCI (n=40, female=20) from the Alzheimer’s Disease Neuroimaging Initiative (ADNI) were analyzed using the Functional Connectivity Toolbox (CONN). Our results demonstrate that connectivity of hippocampus to the precuneus cortex and brain stem was significantly stronger in males than in females. These results improve our current understanding of the role of hippocampus-precuneus cortex and hippocampus-brainstem connectivity in sex differences in MCI. Understanding the contribution of impaired functional connectivity sex differences may aid in the development of sex specific precision medicine to manipulate hippocampal-precuneus cortex and hippocampal-brainstem connectivity to decrease the progression of MCI to AD.